Digital Evidence in Human Rights Violations and International Criminal Justice - Al-Billeh, Tareq; Al-Hammouri, Ali; Khashashneh, Tawfiq; AL Makhmari, Mohammed; Al Kalbani, Hamad (Journal of Human Rights, Culture and Legal System, 2024)
The rapid development of the use of digital technologies has facilitated access to digital information and evidence. This information and digital evidence are obtained via the Internet, social media or satellite. And may be used to investigate violations of human rights and international criminal law. Therefore, there is a problem of rebalancing between the right to privacy and the use of information and digital evidence in the investigation of violations of human rights and international criminal law. This study has objective of unified universal principles that set out the origins and rules for the use of information and digital evidence in the investigation of violations of human rights and international criminal law. In order to ensure international and national justice and criminal accountability and to document all violations of human rights and international criminal law. The analytical approach will be used through analysis of previous studies on the use of digital information and evidence in the investigation of violations of human rights and international criminal law. And analysis of the Berkeley Protocol on Open-Source Digital Investigations. Several findings and recommendations were reached in this paper, the most important of which is the need for the international community to recognize the information and digital evidence obtained to demonstrate violations of human rights and international criminal law.